Titania nanoparticles stabilized HPA in SBA-15 for the intermolecular hydroamination of activated olefins - Sawant-Dhuri, Dhanashri; Balasubramanian, Veerappan V.; Ariga, Katsuhiko; Park, Dae-Hwan; Choy, Jin-Ho; Cha, Wang Soo; Al-deyab, Salem S.; Halligudi, Shivappa B.; Vinu, Ajayan (ChemCatChem, 2014)
A liquid phase hydroamination (HA) of alpha,beta-ethylenic compounds with amines was investigated with TiO2 nanoparticles stabilized 12-tungstophosphoric acid (TPA) in SBA-15. The catalysts were prepared by wet impregnation of TPA/TiO2 nanoparticles into the SBA-15 and calcined at different temperatures. The characterization results reveal that the textural properties and the acidity of the prepared catalysts can be finely controlled with the simple adjustment of the calcination temperature and the structure of the support, decorated with the TiO2 and TPA nanoparticles, was intact even after the modification. The prepared catalysts were investigated for HA of ethyl acrylate with different aromatic and aliphatic amines over a wide range of reaction conditions to optimize the yield and the selectivity of product. It was found that this process is 100% atom efficient and the catalytic performance depended significantly on the loading of TPA over the catalyst and the calcination temperature. Under optimized reaction conditions, the best catalyst, 15 wt% TPA/22.4 wt% TiO2/SBA-15 calcined at 1123 K, offered the highest conversion of p-ethylaniline (70%) with 100% chemo-selectivity to the anti-Markovnikov product, i.e., the mono-addition product. The reaction was heterogeneously catalyzed and no contribution from leached TPA into the reaction was observed.
Keywords: heteropoly acids; hydroamination; mesoporous materials; nanocatalysts

Photocatalytic hydrogen generation and CO2 conversion using g-C3N4 decorated dendritic fibrous nanosilica: role of interfaces between silica and g-C3N4 - Rawool, Sushma A.; Samanta, Anupam; Ajithkumar, T. G.; Kar, Yusuf; Polshettiwar, Vivek (ACS Applied Energy Materials, 2020)
We have synthesized g-C3N4 decorated over dendritic fibrous nanosilica (DFNS). The generation of C-N-Si interfaces by coating each fiber of DFNS with g-C3N4 not only provided high surface area but also affected the optical and electronic properties of the composite. The catalyst synthesis reproducibility issue of g-C3N4 was resolved using a vacuum-sealed quartz tube. The extended light absorption in the visible region, enhanced lifetime of photogenerated charge carriers due to the formation of interfaces between silica and g-C3N4 (confirmed by solid-state NMR), and increased surface area result in the improved photocatalytic activity of DFNS/g-C(3)N(4)for hydrogen generation and CO2 conversion.
Keywords: CO2 conversion; DFNS; g-C3N4; Hydrogen generation; nanocatalysts; photocatalysts; Solid-state NMR

One-pot synthesized efficient molybdenum-niobium-oxide nanocatalyst for selective C-O and C-N coupling reactions at mild conditions - Kalbande, Pavan Narayan; Singh, Nittan; Swapna, Bhattu; Umbarkar, Shubhangi; Sudarsanam, Putla (Catalysis Communications, 2023)
An efficient molybdenum-niobium-oxide nanomaterial was synthesized by a one-pot hydrothermal method for selective C-O (glycerol ketalization) and C-N coupling (benzylamine oxidation) reactions. The catalytically favourable properties, such as defective metal sites, truncated surfaces, and uniform metal dispersion in the MoO3-Nb2O5 nanorods, calcined at 500 degrees C (MoNb OPS-5), were confirmed by Raman, HR-TEM, and STEM-EDX, respectively. Because of improved Lewis/Bronsted acidic strength, the MoNb OPS-5 catalyst showed higher activity in glycerol ketalization and benzylamine oxidation at mild conditions, giving superior selectivity to solketal (97%) and dibenzylimine (99%), respectively. The MoNb OPS-5 catalyst showed high structural stability and considerable good reusability efficacy.
Keywords: C-O and C-N coupling; Glycerol and benzylamine; Mo-Nb-O nanocatalyst; nanocatalysts; One-pot hydrothermal synthesis